2015
DOI: 10.1039/c4nr07103d
|View full text |Cite
|
Sign up to set email alerts
|

Degradable polyphosphoester-based silver-loaded nanoparticles as therapeutics for bacterial lung infections

Abstract: In this study, a new type of degradable polyphosphoester-based polymeric nanoparticle, capable of carrying silver cations via interactions with alkyne groups, has been developed as a potentially effective and safe treatment for lung infections. It was found that up to 15% (w/w) silver loading into the nanoparticles could be achieved, consuming most of the pendant alkyne groups along the backbone, as revealed by Raman spectroscopy. The well-defined Ag-loaded nanoparticles released silver in a controlled and sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 43 publications
(57 reference statements)
5
43
0
Order By: Relevance
“…By this reaction, a range of cyclic phosphotriester having R′ = H and various R groups that include alkyl chains of various size (methyl to octyl) and unsaturated chains (allyl, butenyl, butynyl, acrylate) has been obtained in good purity enough to be polymerized by the ROP process. However, the purification of these monomers that are highly sensitive toward traces of water or other protic species that easily open the ring, remains a tedious step.…”
Section: Synthesis: Organocatalyzed Ring‐opening Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…By this reaction, a range of cyclic phosphotriester having R′ = H and various R groups that include alkyl chains of various size (methyl to octyl) and unsaturated chains (allyl, butenyl, butynyl, acrylate) has been obtained in good purity enough to be polymerized by the ROP process. However, the purification of these monomers that are highly sensitive toward traces of water or other protic species that easily open the ring, remains a tedious step.…”
Section: Synthesis: Organocatalyzed Ring‐opening Polymerizationmentioning
confidence: 99%
“…In addition, let us also mention that the same degradable amphiphilic block terpolymer based on the polyphosphate backbone bearing pendant alkyne, PEGylated alkyne, and alkyl groups has been used to treat bacterial infections (Figure ). Thanks to the strong interaction between the alkyne groups and the silver cations, which are used as an antimicrobial agent, micelles active for the treatment of lung infections have been achieved . The alkyl side chains impart hydrophobicity to the copolymer allowing the formation of micelles that can be additionally loaded with hydrophobic drugs.…”
Section: Applications In Drug Deliverymentioning
confidence: 99%
“…Respiratory diseases currently rank among the top ten causes of death worldwide, and recent research has shown that inhalation is a possible route of delivery for the treatment of respiratory infections [1], [2] and [3]. The growing number of multi-drug resistant strains of bacteria has made imperative the development of new antibiotics and/or novel approaches to deliver existing agents [1].…”
Section: Introductionmentioning
confidence: 99%
“…The growing number of multi-drug resistant strains of bacteria has made imperative the development of new antibiotics and/or novel approaches to deliver existing agents [1]. Efficient and sustained delivery of therapeutic compounds also represents a new approach for the treatment of diseases [1], [2], [3] and [4].…”
Section: Introductionmentioning
confidence: 99%
“…29 With the desire to move toward fully degradable polymer nanoparticle systems, we have recently reported the straightforward synthesis of versatile and degradable polymer platforms making use of polyphosphoester (PPE)-based block copolymers 3032 and demonstrated their potential use as drug delivery vehicles in biomedical applications, such as the in vivo delivery of paclitaxel 33 and antimicrobial agents to the lungs. 34,35 We now report on the development of fully degradable phosphonium-functionalized amphiphilic diblock copolymers and their self-assembly into well-defined micellar systems for siRNA intracellular delivery.…”
Section: Introductionmentioning
confidence: 99%